The Role Of Empathy and Responsiveness of BPJS in Cibabat Hospital Services in Attaning to Increase Consumer Satisfaction - Tamzil, Adil; Lesmana, Virni Alya; Azzahra, Keysanaura Putri; Az-zahra, Gisca Amalia; Susilawati Sugiana, Neng Susi (LPKIA, 2025)
This study aims to analyze the role of empathy and responsiveness in BPJS-related services at Cibabat Hospital in enhancing consumer satisfaction. Recognizing the importance of humane and efficient interactions in healthcare settings, the research explores how these two dimensions influence patients' perceptions and experiences. Utilizing a quantitative approach, the study surveyed 50 BPJS patients through a structured questionnaire designed to measure service quality and satisfaction levels. Data were analyzed using SPSS software, employing descriptive statistics, reliability tests, and multiple regression analysis to determine the strength and significance of empathy and responsiveness as predictors of satisfaction. The findings reveal a positive and significant effect of both empathy and responsiveness on consumer satisfaction. Empathy, demonstrated through attentive listening and emotional understanding, emerged as the stronger contributor, while responsiveness—reflected in prompt service and staff availability—also showed substantial impact. The practical implications of this research highlight the need for targeted training programs for hospital staff, focusing on communication skills, emotional intelligence, and timely service delivery. Hospital management should foster a patient-centered culture that emphasizes these values to boost satisfaction and trust in BPJS services. What sets this study apart is its localized focus on BPJS users within a single hospital, offering nuanced insights into a specific institutional setting that can inform broader policy initiatives.